2017
DOI: 10.3386/w23816
|View full text |Cite
|
Sign up to set email alerts
|

Is There Still Son Preference in the United States?

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 53 publications
3
32
0
Order By: Relevance
“…Parents of first-born girls had slightly fewer children than parents of boys, (which is in line with the recent study of Blau et al 2017), and of particular relevance to our study, the divorce rate for parents with first-born girls was 0.16 percentage points higher (1.04 per cent in relative terms) than the rate for parents with first-born boys. Note: Authors' estimates of average characteristics of couples with first-born sons and daughters born in 1995-2015.…”
Section: Is the First-born Child's Gender Random?supporting
confidence: 77%
“…Parents of first-born girls had slightly fewer children than parents of boys, (which is in line with the recent study of Blau et al 2017), and of particular relevance to our study, the divorce rate for parents with first-born girls was 0.16 percentage points higher (1.04 per cent in relative terms) than the rate for parents with first-born boys. Note: Authors' estimates of average characteristics of couples with first-born sons and daughters born in 1995-2015.…”
Section: Is the First-born Child's Gender Random?supporting
confidence: 77%
“…For example, econometrics research has identified several differences between U.S. parents of girls versus boys, including a higher divorce rate and differential monetary investment in families [ 70 ]. Other research suggests subtle gender preference may vary by nativity, with first- and second-generation American immigrants showing a greater preference for boys [ 71 ]. It is thus plausible that cultural factors that track with race/ethnicity or nativity could have contributed to the difference in the magnitude of association that we observed between our diverse cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…For example, econometrics research has identi ed several differences between U.S. parents of girls versus boys, including a higher divorce rate and differential monetary investment in families (70). Other research suggests subtle gender preference may vary by nativity, with rst-and second-generation American immigrants showing greater preference for boys (71). It is thus plausible that cultural factors that track with race/ethnicity or nativity could have contributed to the difference in the magnitude of association that we observed between our diverse cohorts.…”
Section: Discussionmentioning
confidence: 63%